Coronary artery ectasia presenting with acute inferior wall myocardial infarction in a young adult - Htun Latt; Sammy Aung; Kyaw Kyaw; Richard Seher (Greater Baltimore Medical Center, 2017)
Coronary artery ectasia (CAE), a variant of coronary artery anomalies, is a rare clinical entity. Although atherosclerotic coronary artery disease (CAD) is the most common cause of acute coronary syndrome (ACS), CAE also conveys a relatively high risk for potentially life-threatening cardiac events. We report a case of a 35-year-old male with two-vessel CAE, who presented with acute inferior wall ST election myocardial infarction (STEMI). After initiating medical therapy including bivalirudin, emergent percutaneous coronary intervention (PCI) with stenting of postero-lateral branch of right coronary artery (RCA) was performed. Coronary angiography also showed diffuse ectasia of RCA and left anterior descending artery (LAD). The patient tolerated the procedure well and was discharged on appropriate medical therapy. He was followed-up at one month, with no resulting cardiac events. This case highlights the importance of CAE awareness. CAE has drawn the attention of clinicians because of its clinical implications, as well as its seemingly higher prevalence, due to the abundant use of coronary angiograms and advanced cardiac imaging in the contemporary world. Albeit there has been much progress in the understanding and management of the disease, questions still remain regarding the exact pathophysiology, management guidelines and prognosis of CAE, which are worth further study.